A new strain of Rhodococcus indonesiensis T22.7.1T and its functional potential for deacetylation of chitin and chitooligsaccharides - Xie, Junjie; Yin, Doudou; Ou, Junchao; Lu, Bo; Liao, Siming; Yang, Dengfeng; Zhang, Hongyan; Shen, Naikun (Frontiers in Microbiology, 2024)
Introduction Chitin, abundant in marine environments, presents significant challenges in terms of transformation and utilization. A strain, T22.7.1T, with notable chitin deacetylation capabilities, was isolated from the rhizosphere of Acanthus ebracteatus in the North Sea of China. Comparative 16S rDNA sequence analysis showed that the new isolate had the highest sequence similarity (99.79%) with Rhodococcus indonesiensis CSLK01-03T, followed by R. ruber DSM 43338T, R. electrodiphilus JC435T, and R. aetherivorans 10bc312T (98.97%, 98.81%, and 98.83%, respectively). Subsequent genome sequencing and phylogenetic analysis confirmed that strain T22.7.1T belongs to the R. indonesiensis species. However, additional taxonomic characterization identified strain T22.7.1T as a novel type strain of R. indonesiensis distinct from CSLK01-03T. Methods This study refines the taxonomic description of R. indonesiensis and investigates its application in converting chitin into chitosan. The chitin deacetylase (RiCDA) activity of strain T22.7.1T was optimized, and the enzyme was isolated and purified from the fermentation products. Results Through optimization, the RiCDA activity of strain T22.7.1T reached 287.02 U/mL, which is 34.88 times greater than the original enzyme’s activity (8.0 U/mL). The natural CDA enzyme was purified with a purification factor of 31.83, and the specific activity of the enzyme solution reached 1200.33 U/mg. RiCDA exhibited good pH and temperature adaptability and stability, along with a wide range of substrate adaptabilities, effectively deacetylating chitin, chitooligosaccharides, N-acetylglucosamine, and other substrates. Discussion Product analysis revealed that RiCDA treatment increased the deacetylation degree (DD) of natural chitin to 83%, surpassing that of commercial chitosan. Therefore, RiCDA demonstrates significant potential as an efficient deacetylation tool for natural chitin and chitooligosaccharides, highlighting its applicability in the biorefining of natural polysaccharides.